Insulin sensitivity affects propensity to obesity in an ethnic-specific manner: results from two controlled weight loss intervention studies - Gower, Barbara A (BioMed Central, 2013)
BACKGROUND: Risk for obesity differs with ethnicity/race and is associated with insulin sensitivity (S(I)), insulin responsiveness, and dietary glycemic load (GL). The objective of this study was to test the hypotheses that, 1) obesity-prone, normal weight, African-American (AA) women would be more insulin sensitive than BMI-matched, never overweight AA women; 2) increased adiposity over time would be associated with greater baseline S(I) and higher dietary GL in AA but not European-American (EA) women; and 3) increased adiposity over time would be predicted by S(I) in women with high but not low acute insulin response to glucose (AIRg). METHODS: Two controlled weight loss interventions were conducted involving overweight (BMI 25.0-29.9 kg/m(2)) premenopausal AA and EA women. The first included matching with normal-weight (BMI <25.0 kg/m(2)) controls following weight loss, and then comparing S(I). The second included a 1-year follow-up of weight-reduced participants to identify predictors of change in %body fat. Main outcome measure in the first study was insulin sensitivity (S(I)) as assessed with intravenous glucose tolerance test (IVGTT), and in the second study was change in %fat, as assessed with DXA, over one year. AIRg was assessed during IVGTT, and free-living diet was determined by food record. RESULTS: In the first study, formerly overweight AA women were 43% more insulin sensitive than BMI-matched never overweight AA (P < 0.05). In the second study, S(I) was positively associated with change in %fat over 1 year only in AA women (P < 0.05) and women with high AIRg (P < 0.05). In addition, AA who were insulin sensitive and who consumed a higher GL diet tended to gain greater %fat (P = 0.086 for diet x S(I) interaction). In both studies, AA women had higher AIRg (P < 0.001) than EA women. CONCLUSIONS: Formerly overweight (obesity-prone) AA women were more insulin sensitive than never overweight AA women, a quality that may predispose to adiposity, particularly when combined with a high GL diet. This ethnicity/race-specific effect may be due to high insulin responsiveness among AA.